Health service quality of human immunodeficiency virus voluntaries’ counselling and testing - Sudirman, Sudirman; Purwiningsih, Sri; Darmin, Darmin; Susianawati, Desak Eka; Arni, Fitri; Fajrah, Sitti (International Journal of Public Health Science (IJPHS), 2023)
United Nations & AIDS (UNAIDS) in 2019 stated that 38 million individuals in the world were suffering from human immunodeficiency virus or HIV. Since it was discovered in 1987, the number of HIV cases in Indonesia until mid-2020 was 436,948 cases, of which 64,990 people have died. This study aims to assess the quality of health services with the service quality (SERVQUAL) analysis model on voluntary HIV counseling and testing. A quantitative study was conducted with a descriptive observational analytic approach and a cross-sectional design on 120 respondents. The variables were measured using a service quality questionnaire and Likert scale. The results showed a difference between the expectations and perceptions of respondents on the service quality of voluntary HIV counseling and testing. The statistical analysis (p=0.000) shows that the health services for voluntary HIV counseling and testing have poor quality. However, the respondents gave good scores on responsiveness and assurance of the services. Managers and relevant authorities need to plan and pay special attention to other yet optimal variables.